PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR TEMATIK DI SD - Elvani Hertati; Kartono Kartono; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to analyze and prove the influence of the problem- based learning models in thematic learning on student learning outcomes in fifth grade of the Mujahidin Elementary School South Pontianak. The research method used was an Experiment, a form of Quasi Experimental type of NonEquivalent Control Group Design. The sampling technique used Purposive Sampling. The techniques used in data collection are measurements with research instruments in the form of multiplechoice test to measure cognitive domain, affective domain using attitude assessment sheets, and psychomotor domain using psychomotor assessment sheets. The results of data analysis are, cognitive domain the average score of the learning outcomes experiment class 71,36 and the control class is 65,50. After the t-test is obtained tcount (2,8761) > ttable (2,0042) then Ha is accepted. Affective domain the average score of the learning outcomes experiment class 76,28 and the control class is 75,4. After the t-test is obtained tcount (1,6714) < ttable (2,0042) then Ho is accepted.  Psychomotor domain the average score of the learning outcomes experiment class 75,8957 and the control class is 73,00. After the t-test is obtained tcount (4,4829) > ttable (2,0042) then Ha is accepted. From the calculation of the effect size obtained at 0.52. This means that the problem-based learning models has a medium influence on student learning outcomes in thematic learning in the fifth grade of Mujahidin Elementary School South Pontianak. Keywords: Learning Outcomes, Problem Based Learning Models, Thematic Learning